Pharmacokinetics of imidocarb in normal dogs and goats - Abdullah, Abdul Salam; Baggot, J. Desmond (Wiley, 1983)
The pharmacokinetics of imidocarb was studied in seven mongrel dogs and eight crossbred goats. An intravenous bolus dose (4 mg/kg) of 12% imidocarb dipropionate solution was injected into the cephalic vein in dogs and the jugular vein in goats. The plasma concentration of imidocarb was measured by spectrophotometry. The experimental data were analysed using a two-compartment open model. The apparent volume of the central compartment was significantly higher (P<O.O 1) in dogs than in goats. The significantly larger (P<0.05) apparent specific volume of distribution in goats than in dogs may be attributed to passive diffusion followed by ion trapping of the drug in rumen fluid. Neither the half-life nor body clearance differed significantly between dogs (tl/2' 207 ± 45 min; CIB, l.47 ± 0.38 ml/min kg) and goats (tY2' 251 ± 94 min; CtB, 1.62 ± 0.50 ml/min kg). While almost 80% of the dose had been eliminated at 8 h in both species, the high ratio of the imidocarb level in the peripheral-to-central compartment in goats suggests that a prolonged period may be required for complete elimination of the drug.